Analisis Pengaruh Kepatuhan dan Kesadaran Mahasiswa terhadap Bahaya Asap Rokok pada Kawasan Tanpa Rokok di FISIP USU - Harahap, Aisyah Rinjani; Rosselvelt, Franklin Asido; Aisyah, Dara; Safitri, Ani; Siadari, Irwan Maruli; Simatupang, Keyko Imelda; Siregar, Nabila Sakila (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2025)
The Smoke-Free Area (Kawasan Tanpa Rokok/KTR) policy is implemented as an effort to create a healthy academic environment free from cigarette smoke. However, its enforcement still faces challenges, particularly regarding students' compliance and awareness. This study aims to analyze the influence of compliance and awareness regarding the dangers of cigarette smoke and how these variables affect smoking behavior and comfort within the smoke-free area at the Faculty of Social and Political Sciences, Universitas Sumatera Utara. This research applies a quantitative survey method with 30 participating students. The research instrument was examined through validity and reliability testing, classical assumption testing, and further analyzed using multiple linear regression. The findings indicate that students’ awareness has a significant influence on smoking behavior and compliance with KTR regulations, while compliance without awareness does not significantly affect smoking behavior. Additionally, both awareness and compliance simultaneously contribute to students’ comfort in the smoke-free environment. These results suggest that effective implementation of smoke-free policies requires not only rules and enforcement but also continuous education to strengthen awareness. Therefore, strengthened regulation combined with health promotion strategies is necessary to support the development of a healthy campus culture.